Anxiolytic and antidepressant-like effects of Annona coriacea (Mart.) and caffeic acid in mice. (February 2020) - Monteiro, Álefe Brito; Kelly de Souza Rodrigues, Cristina; Petícia do Nascimento, Emmily; Sales, Valterlúcio dos Santos; de Araújo Delmondes, Gyllyandeson; Nogueira da Costa, Maria Haiele; Pereira de Oliveira, Victor Afonso; Pereira de Morais, Luis; Boligon, Aline Augusti; Barbosa, Roseli; Martins da Costa, José Galberto; Alencar de Menezes, Irwin Rose; et al.
Abstract: This research evaluated the anxiolytic and antidepressant-like effects of a hydroethanolic extract from the leaves of Annona coriacea (EHFAC) and caffeic acid (CA). Mice were intraperitoneally treated with saline, EHFAC (1, 10, 20 mg/kg) or CA (0.15 mg/kg) and subject to the elevated plus-maze, open field, rota-rod, forced swimming and reserpine-induced akinesia tests. Pro-convulsant and anticholinergic effects were also evaluated. EHFAC presented anxiolytic-like effect on the elevated plus-maze, which was partially reversed by flumazenil. A similar effect was observed with CA. In the forced swimming test, EHFAC and CA reduced the immobility time of mice; such effect was potentiated when EHFAC or CA were associated with imipramine, bupropion and fluoxetine. The antidepressant-like effect was reinforced as EHFAC partially reversed the reserpine-induced akinesia. In addition, a pre-treatment with EHFAC and CA did not decrease the latency to 1st seizure of animals that received a sub-convulsive dose of PTZ, nor reduced the intensity of oxotremorine-induced tremors. Taken together, the results indicate that EHFAC and CA have anxiolytic and antidepressant-like effects, which involve important neurotransmitter systems, such as GABAergic and monoaminergic ones, being devoid of side effects, commonly associated with classical psychotropic drugs. Highlights: Anxiolytic and antidepressant-like effects are reported. Possible involvement of the GABAergic and monoaminergic systems. Devoid of side effects commonly associated with classical psychotropic drugs.